Dancing with a Difference: Reconfiguring the Poetic Politics of Aboriginal Ritual as National Spectacle - Magowan, Fiona (The Australian journal of anthropology, 2000)
This paper argues that indigenous dance is a poetic politics of cross-cultural encounter that engages Aboriginal identities with those of the Australian nation. I question the nature of this encounter in terms of a performative dialogue that is both musically and kinesically presented by indigenous communities and ‘translated’ into political discourse by the government. The sentiments of ‘translation’ raise questions as to how local ritual expressions of Aboriginal dance can mediate dialogue when presented as national spectacle. What is being meditated? What is happening in the process of evocation? In this performative nexus, I focus specifically on the poetic politics of Yolngu ritual as spectacle; the nature of performative dialogue in terms of shared dance forms between indigenous communities; the problem of the authentication of dance identities; and how corporeal dispositions of indigenous dance genres influence national sentiment by their symbolic power. I pursue these issues through an analysis of how ancestral dances have been repositioned in national performance venues, such as concerts, cultural centres and ritual arenas, as a means of asserting performative statements about indigenous positioning within the nation-state. The nature of this dialogue raises questions of authenticity and processes of authentication. It highlights indigenous concerns to control representations of indigeneity as national event, as well as a desire to convey something of the sentiment and sentience embodied in the poetics of their ancestral performances.